Comprehensive Review on Analytical Profile of Antidepressant Drug - Chaudhari, Kamlesh Raju; Bhaskar, Rajveer; Ola, Monika; Patil, Amod; Ambatkar, Ankita; Mahajan, Tejaswini (Journal of Drug Delivery and Therapeutics, 2020)
Venlafaxine is an antidepressant belonging to a group of drugs called selective serotonin and norepinephrine reuptake inhibitors (SSNRIs). Venlafaxine affects chemicals in the brain that may be unbalanced in people with depression. It is used to treat major depressive disorder, anxiety and panic disorder. The present review assesses the various approaches for analysis of Venlafaxine in bulk drug as well as various formulations. A concise review represents the compilation and discussion of about more than 35 analytical methods which includes HPLC, HPTLC, UPLC, LC-MS and UV-Spectrophotometry methods implemented for investigation of Venlafaxine in biological matrices, bulk samples and in different dosage formulations. This detailed review will be of great help to the researcher who is working on Venlafaxine.Keywords: Venlafaxine; Analytical Profile; HPLC; HPTLC; Bioanalytical; Stability indicating